2021
DOI: 10.31083/j.jin2003063
|View full text |Cite
|
Sign up to set email alerts
|

The impact of CRMP4 SUMOylation on the Cav1.2 interaction, neurite outgrowth and thermal pain sensitivity

Abstract: Collapsin response mediator protein 4 (CRMP4) is critical for neuronal development. However, whether CRMP4 could be SUMOylated and how the SUMOylation regulates the interaction with the L-type voltage-gated calcium channel (Cav1.2), neurite outgrowth, and thermal pain sensitivity remain to be elucidated. To determine the SUMOylation of CRMP4, Glutathione S-transferase (GST) -Small Ubiquitin-like Modifier 1 (-SUMO1), -SUMO2, and -SUMO3 proteins were purified for GST-pulldown. Immunofluorescence staining was per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Following a previous study [ 30 ], the processed HUVECs were seeded onto polylysine-coated slides in 24-well plate. After 48 h, cells were fixed with 4% paraformaldehyde and permeabilized by 0.1% Triton X100.…”
Section: Methodsmentioning
confidence: 99%
“…Following a previous study [ 30 ], the processed HUVECs were seeded onto polylysine-coated slides in 24-well plate. After 48 h, cells were fixed with 4% paraformaldehyde and permeabilized by 0.1% Triton X100.…”
Section: Methodsmentioning
confidence: 99%
“…CRMP2 is known to be sensitive to divalent cations, which affect the stability of the CRMP2 tetramer and the propensity to form heterotetramers with other CRMP isoforms which share high sequence identity (∼75% for CRMPs 1–4) and very high structural similarity. , Further, CRMP4 has also been reported to be a member of synaptic vesicle recycling complexes . In our hands, expression of eGFP-CRMP4 in neurons resulted in an increase in calcium currents that was even higher than that of eGFP-CRMP2, implicating CRMP4 as an additional regulator of calcium channels, as also suggested in another study . In fact, our earliest study actually lists the CRMP1 isoform as being found in the presynaptic Ca V 2.2 complex from rat brain synaptosomes .…”
Section: Future Directionsmentioning
confidence: 51%
“…188 In our hands, expression of eGFP-CRMP4 in neurons resulted in an increase in calcium currents that was even higher than that of eGFP-CRMP2, implicating CRMP4 as an additional regulator of calcium channels, 189 as also suggested in another study. 190 In fact, our earliest study actually lists the CRMP1 isoform as being found in the presynaptic Ca V 2.2 complex from rat brain synaptosomes. 85 Potentially, a heteromeric form with CRMP1 could have been identified in that analysis as later work showed that CRMP1 is not involved in regulation of Ca V 2.2 7 but can form heterotetramers with CRMP2.…”
Section: ■ Future Directionsmentioning
confidence: 99%
See 2 more Smart Citations